1949
DOI: 10.1039/tf9494500085
|View full text |Cite
|
Sign up to set email alerts
|

The thermal decomposition of explosives. Part II. Cyclotrimethylenetrinitramine and cyclotetramethylenetetranitramine

Abstract: The decomposition of both liquid cyclotrimethylenetrinitramine (cyclonite) and cyclotetramethylenetetranitramine follows the unimolecular equation, the Arrhenius frequency factors being very large. The unimolecular uncatalysed decomposition of cyclonite in dilute solution in dicyclohexyl phthalate and trinitrotoluene has a frequency factor approaching the normal value. A more concentrated solution of cyclonite decomposes faster than the dilute solutions ; this fact and the anomalous frequency factor for the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 0 publications
6
38
0
Order By: Relevance
“…Comparison of the kinetic parameters of heat release in the condensed phase of HMX (points 1) and HMX decomposition in the nitrobenzene solution (curve 2[49]), acetone (curve 3[50]), and melt (curves 4[51] and 5[52]). …”
mentioning
confidence: 99%
“…Comparison of the kinetic parameters of heat release in the condensed phase of HMX (points 1) and HMX decomposition in the nitrobenzene solution (curve 2[49]), acetone (curve 3[50]), and melt (curves 4[51] and 5[52]). …”
mentioning
confidence: 99%
“…Thus, RDX molecules dissociate according to pathways that are determined both by concerted symmetrical triple ®ssion and by N±N bond scission. It is still disputable whether these reactions control the decomposition of RDX and HMX in the condensed phase and whether reactions between adjacent molecules are important, as was originally suggested by Robertson (5) . The temperature dependence of formation rates for the gaseous products released during the pyrolysis of HMX was determined by simultaneous thermogravimetric modulated beam mass spectrometry (9) .…”
Section: Computer Modeling Experimental Data Results and Discussionmentioning
confidence: 97%
“…Robertson (5) originally proposed elimination of formaldehyde as the initial step of decomposition in solution. His results showed that such decomposition displays monomolecular behavior, whereas pure RDX and HMX exhibited the effect of neighboring molecules.…”
Section: Computer Modeling Experimental Data Results and Discussionmentioning
confidence: 99%
“…Arrhenius expressions for the temperature effect on the rate constant have been cited for thermal decomposition of HMX in the solid -phase Medvedev, 1977) and in the liquid phase " to be published; Robertson, 1949). Fol-"lowing is an expression for the rate constant which is applicable to both solid and liquid phase thermal decomposition of IMX:…”
Section: Hmmentioning
confidence: 99%
“…The e. following are expressions for the rate constant (k) : A number of kinetic studies have been performed on the thermal decomposition of RDX. The rate of thermal decomposition of RDX has been shown to follow first order kinetics (Schroeder --to be published;Urbanski, 1964;Robertson, 1949) although complex kinetics may be observed under some conditions (Schroeder, 1979;Schroeder --to be published).…”
mentioning
confidence: 99%